The Impact of Overconfidence Bias on Strategic Decision-Making - Till Ebeling,Maximilian; Montesinos Martinez,Miguel (2025)
Strategic decision-making (SDM) is a core function of managerial roles, often carried out under pressure, uncertainty, and cognitive limitations. This thesis explores how overconfidence bias affects strategic decision-making in organisational settings. While cognitive biases have been extensively studied in psychology and behavioural economics, the specific impact of overconfidence on business-related strategic decisions has received limited empirical attention. By using an experimental vignette method, this study investigates how overconfidence bias influences the strategic decision-making of business students. The results indicate that participants influenced by overconfidence bias significantly make different decisions compared to those deciding under more neutral conditions. Those findings underscore the importance of metacognitive awareness in fostering more deliberate and balanced strategic choices. Given the subtle nature of such biases, their effects often go unnoticed, highlighting the need for a deeper reflection on how to make well-balanced strategic decisions.
Keywords: strategic decision-making; rationality; bounded rationality; dual-process theory; heuristics; overconfidence bias; quantitative method; vignette study